INOVASI PEMBELAJARAN ALJABAR RING MELALUI LESSON STUDY - Karsoni Berta Dinata (Universitas Muhammadiyah Kotabumi, 2018)
Subject Algebra Ring or Algebra Abstract has abstract characteristics and requires a variety of supporting knowledge to learn it. Abstract characteristic in the material of algebra ring requires a lecturer to innovate creatively, pack material to be easily understood by the students and design the learning that can improve the students' capabilities. Learning innovation should be done continuously by reflecting the effectiveness of the learning that has been done. Lesson Study facilitates the quality of learning to be improved through the cycle 1) Plan (Plan), 2) do (perform), and see (reflect), which is done collaboratively and with the collegial principle. Lesson Study gives a positive impact so that the dynamic mathematics learning can be implemented.